PENERAPAN SISTEM PENGELOLAAN BARANG MILIK DAERAH & KEWAJARAN LAPORAN KEUANGAN PEMERINTAH DAERAH: STUDI PADA PEMERINTAH DAERAH PROVINSI JAWA BARAT - Sayekti, Fitria Ningrum (EKUBIS: Jurnal Ekonomi, Keuangan, & Bisnis, 2020)
This study was conducted to determine whether there are significant implementation sectoral asset management systems to the fairness of the financial statements of the Local Government. This research was conducted at SKPD in West Java province with a population of 47 SKPD, which consists of the Department, Agency and Institutions in West Java province with a sample using stratified random sampling amounted to 26 respondents. The method used is survey method with descriptive associative approach and using simple linear regression analysis. Results of the correlation coefficient calculation declare the application of sectoral asset management systems affect the fairness of the financial statements of Local Government in West Java province with a value of 0.632 is interpreted "strong".